Anti-hyperlipidemic and antioxidant effects of alkali-extractable mycelia polysaccharides by Pleurotus eryngii var. tuolensis. (1st November 2017) - Ren, Zhenzhen; Li, Juan; Xu, Nuo; Zhang, Jianjun; Song, Xinling; Wang, Xiuxiu; Gao, Zheng; Jing, Huijuan; Li, Shangshang; Zhang, Chen; Liu, Min; Zhao, Huajie; et al.
Highlights: The TC and TG levels on mice decreased to 2.48 ± 0.08 and 1.24 ± 0.03 mmol/L by Al-MPS (500 mg/kg bw). Glucose played vital roles in guaranteeing the pharmacological effects. Al-MPS showed both α- and β-anomeric configurations by the NMR analysis (103.58–93.22 ppm). Findings indicated Al-MPS had potential values in applying functional foods. Abstract: In this study, we noted that the Al-MPS from Pleurotus eryngii var. tuolensis provoked pharmacological effects on blood lipid profiles and oxidative stress. Animal studies demonstrated that Al-MPS showed potential effects on relieving hyperlipidemia and preventing oxidative stress, reflecting by decreasing the levels of serum enzyme activities (ALP, ALT and AST), restoring the activities of antioxidant enzymes (SOD, GSH-Px, CAT and T-AOC), down-regulating the MDA and LPO contents, as well as remitting the hepatic and cardiac tissues injury, respectively. The serum levels of TC, TG, LDL-C, VLDL-C, and HDL-C on mice treated with Al-MPS (500 mg/kg bw) reached 2.48 ± 0.08, 1.24 ± 0.03, 0.84 ± 0.02, 0.34 ± 0.02, and 1.80 ± 0.03 mmol/L, which were lower/higher against the hyperlipidemia mice. The results clearly indicated that the Al-MPS could be used as a beneficial health food and potentially natural candidate medicine in preventing the high-fat emulsion-induced hyperlipidemia.